2014
DOI: 10.1021/ie403956d
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble Acrylamide Sulfonate Copolymer for Inhibiting Shale Hydration

Abstract: Here we report a water-soluble acrylamide sulfonate copolymer for inhibiting shale hydrate formation. The copolymer, denoted as PANAA, was synthesized via copolymerization of acrylamide (AM), N,N-diallylbenzylamine (NAPA), acrylic acid (AA), and 2-(acrylamide)-2-methylpropane-1-sulfonic acid (AMPS). The performance of this new water-soluble copolymer for inhibiting shale hydration was investigated for the first time. The retention ratio of apparent viscosity of 2 wt % PANAA solution can reach 61.6% at 130 °C a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…36 To sum up, hydration damage is associated with external conditions and its evaluation should include these influence factors. hydration activity, thus inhibiting hydration.…”
Section: Den H Denmentioning
confidence: 99%
“…36 To sum up, hydration damage is associated with external conditions and its evaluation should include these influence factors. hydration activity, thus inhibiting hydration.…”
Section: Den H Denmentioning
confidence: 99%
“…Bis (hexamethylene) triamine [33] • Protonation of multiple amine groups is the main inhibition mechanism. Copolymers [34][35][36] • Exhibiting excellent temperature resistance and salt-tolerance. Henna extract [37] • The first proposed plant-based clay stabilizer.…”
Section: Silicatesmentioning
confidence: 99%
“…[19,20] Xu et al used the XRD instrument to determine the interplanar spacing of clay minerals and found that XRD was a feasible, fast and intuitive method to assess the anti-swelling and swelled clay shrinkage property of clay stabilizers. [12] Warr used in situ wet-cell X-ray diffraction to determine the mechanism and rate of hydration swelling during the infiltration of natural waters into pressed bentonite powders within a confined reaction volume. [21] Guo et al found that XRD can be used to intuitively and realistically evaluate the inhibition of the clay swelling.…”
Section: Xrd Testmentioning
confidence: 99%
“…[22] Liu et al used XRD measurement to evaluate shrinkage property of copolymer PANAA on the swelled clay. [12] The interplanar spacing of Na-MMT of clay samples in different solutions was investigated by X-ray diffractometer. As can be seen from Fig.…”
Section: Xrd Testmentioning
confidence: 99%
See 1 more Smart Citation